Degradation of rhodamine B in a novel bio-photoelectric reductive system composed of Shewanella oneidensis MR-1 and Ag3PO4. (May 2019) - Xiao, Xiang; Ma, Xiao-Lin; Liu, Zhao-Ying; Li, Wen-Wei; Yuan, Hang; Ma, Xiao-Bo; Li, Li-Xia; Yu, Han-Qing
Abstract: Photocatalytic catalysis is widely used for pollutant degradation. Since some pollutants with oxidative nature are readily reduced rather than oxidized and reductive reaction caused by photogenerated electrons is limited in the presence of oxygen, photocatalytic reduction process is more applicable for the degradation of pollutants with oxidative nature than oxidation. In this work, a novel bio-photoelectric reductive degradation system (BPRDS), composed of an electrochemically active bacterium Shewanella oneidensis MR-1 and a visible-light photocatalyst Ag3 PO4, was established under anaerobic conditions and its photodegradation performance was evaluated through degrading rhodamine B (RhB), a typical organic pollutant. The as-synthesized Ag3 PO4 nanoparticles exhibited absorption in the entire visible spectral range of 400–800 nm. RhB could be degraded in BPRDS with visible light irradiation under anaerobic conditions, but not be decomposed in the absence of Shewanella cells. Block of Mtr respiratory pathway, a transmembrane electron transport chain, resulted in a reduction in degradation rate of RHB in BPRDS. Dose of riboflavin also substantially decreased the RhB degradation. These results suggest that the electrons released by Shewanella were involved in the RhB photodegradation, which was achieved via a stepwise N -deethylation process. In BPRDS, RhB was degraded by photoreduction, rather than photooxidation. This work is useful to develop integrated physico-chemical-microbial systems for pollutant degradation, facilitate better understanding about the biophotoelectric reductive degradation mechanisms and beneficial to their applications for environmental remediation. Graphical abstract: Unlabelled Image Highlights: A bio-photoelectric reductive degradation system (BPRDS) was constructed. RhB was anaerobically degraded by BPRDS under visible light excitation. Electrons released by Shewanella were essential for the BPRDS operation. Shewanella acted as the hole scavenger in the photoexcitation of Ag3 PO4 .